Uterine preservation with Alcides-Pereira's compressive sutures for postpartum uterine atony. (October 2022) - Santos, Rita Rosado; Martins, Inês; Clode, Nuno; Santo, Susana
Abstract: Introduction: Postpartum hemorrhage (PPH) is mostly caused by uterine atony and is the leading cause of maternal death. Hysterectomy may be necessary in severe cases, but uterine compressive sutures are an uterine-sparing alternative. In 2005, Alcides Pereira proposed a technique with serial superficial stiches around the uterus. To date, there were no further reports on its clinical use. Objective: To evaluate a tertiary center's experience with Alcides-Pereira's compressive uterine sutures for severe PPH due to uterine atony, reviewing its efficacy, morbidity, and impact on reproductive outcomes. Study Design: An 11-year retrospective cohort study of Alcides-Pereira's sutures for PPH at a single tertiary hospital. Demographic and obstetric data were collected. Details of subsequent pregnancies and fertility plans were collected through a telephonic interview. Comparison between women in which the sutures were effective and ineffective to prevent hysterectomy was made. Results: Alcides-Pereira's sutures were applied in 23 patients with PPH due to uterine atony. The technique was successful in controlling the hemorrhage and avoiding hysterectomy in 20 patients (87%). When successful, the sutures avoided the need for any blood therapy in 55% (RR 0.45, 95% CI 0.28–0.73) of patients, intensive care unit admission in 80% (RR 0.2, 95% CI 0.08–0.48) and significantly shortened the length of hospital stay. All patients with preserved uterus resumed their usual menstrual pattern. One had a subsequent term vaginal delivery; one had three first trimester miscarriages. All other patients did not try to conceive. Conclusion: Alcides-Pereira's sutures are a feasible, uterine-sparing technique, providing an effective and safe option for PPH.